2021
DOI: 10.1080/13880209.2021.1920619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic assessment of mechanisms underlying anti-renal fibrosis properties of petroleum ether extract from Amygdalus mongolica

Abstract: Context:The petroleum ether extract (PET) of Amygdalus mongolica (Maxim.) Ricker (Rosaceae) has an ameliorative effect on renal fibrosis (RF). Objective: To evaluate the antifibrotic effects of A. mongolica seeds PET on RF by serum metabolomics, biochemical and histopathological analyses. Materials and methods: Sixty male Sprague-Dawley rats were randomly divided into the sham-operated, RF model, benazepril hydrochloride-treated model (1.5 mg/kg) and PET-treated (1.75, 1.25, 0.75 g/kg) groups, and the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Recent studies showed that BUT of A. mongolica was effective in the prevention of RF (5,(13)(14)(15)(16). However, the optimal dose and the mechanisms underlying the antifibrotic effects of BUT are still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies showed that BUT of A. mongolica was effective in the prevention of RF (5,(13)(14)(15)(16). However, the optimal dose and the mechanisms underlying the antifibrotic effects of BUT are still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical assays were performed to assess the effect of drug treatment on the kidney functions of rats. For positive control, we chose benazepril, an angiotensin II inhibitor that reduces plasma aldosterone levels, increases vasodilatation, lowers blood pressure, relieves oxidative stress, increases glomerular filtration rate and reduces proteinuria (5). As shown in Fig.…”
Section: Effects Of N-butanol Extract On Biochemical Indexes Levelsmentioning
confidence: 99%
See 3 more Smart Citations